Tradisi Barabab Dalam Kehidupan Masyarakat Di Nagari Koto Nan Duo Kecamatan Batang Kapas Kabupaten Pesisir Selatan - Yohanis; Jafrimanedi; gusnayetti (LPPM STISIP IMAM BONJOL, 2026)
The purpose of this research is to explain and describe the values contained within the barabab tradition in Nagari Koto Nan Duo, Batang Kapas District. This study uses a descriptive qualitative method to provide a detailed picture of the issue through scientific analysis, aligning with the actual conditions to determine the values embedded in the barabab tradition. Based on the findings in the field, it is shown that the values contained in the barabab tradition are composed of four aspects: (a) Social Value, which refers to the sense of togetherness or social interaction among the community; (b) Artistic Value, representing the aesthetic beauty produced by the players or artists in performing the rabab and delivering the kaba (story); (c) Cultural Value, which is the custom passed down through generations; and (d) Moral Value, involving the formation of community attitudes based on the stories and tales conveyed by the rabab players. This ancestral tradition, inherited from generation to generation, has led the community to agree to the preservation of the barabab tradition.